2005
DOI: 10.1111/j.1525-1470.2005.22104.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Tumors as the Initial Presentation of Non‐T, Non‐B, Nonmyeloid CD4+ CD56+ Hematolymphoid Malignancy in an Adolescent Boy

Abstract: We describe a 14-year-old Hispanic boy who presented with a 2-month history of enlarging plum-colored cutaneous tumors on his face, trunk, and proximal extremities. Histopathologic examination showed nodular infiltrates of malignant mononuclear cells extending from the superficial dermis to the deep subcutis. Immunohistochemical staining of the biopsy specimen and flow cytometry studies on a bone marrow aspirate revealed a CD4+, CD56+ hematolymphoid tumor that was negative for all other myeloid and lymphoid ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The majority of the patients were older adults 2,6,7,29,30 but the disease may occur in younger adults or in children as also previously reported. 2,7,9,25,[31][32][33][34] Most patients presented with cutaneous lesions at initial examination, 2,6 which spread within a few months to involve general areas of the cutis, and blood, bone marrow, and lymph nodes. 8 Cytopenia, especially thrombocytopenia, was common 2,9,29,30,35 and leukocytosis was also noted in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients were older adults 2,6,7,29,30 but the disease may occur in younger adults or in children as also previously reported. 2,7,9,25,[31][32][33][34] Most patients presented with cutaneous lesions at initial examination, 2,6 which spread within a few months to involve general areas of the cutis, and blood, bone marrow, and lymph nodes. 8 Cytopenia, especially thrombocytopenia, was common 2,9,29,30,35 and leukocytosis was also noted in some patients.…”
Section: Discussionmentioning
confidence: 99%
“… 1 A wide spectrum of clinical presentations have been described, ranging from a single nodule to widespread cutaneous manifestations. Fass et al 10 reported a case in which multiple cutaneous tumors were dispersed on the face, trunk, and extremities. In the largest case series to date by Julia et al, 11 most patients (73%) presented with nodular lesions only, whereas other patients had bruise-like patches (12%) or mixed lesions including macules and nodules (14%).…”
Section: Discussionmentioning
confidence: 99%
“…Patients are mostly adults and elderly, although cases in younger individuals, including small children, have been reported [12][13][14][15][17][18][19][20][21]. There is a predominance of males.…”
Section: Clinical Featuresmentioning
confidence: 99%